Time warp : the seventh journey through time - Stilton, Geronimo (Stilton, Geronimo. Journey through time (Series), 2020)
When pirate cats threaten Mouse Island, Professor von Volt sends Geronimo Stilton and his friends back through time to ancient Greece, Atlantis, and Stonehenge to try and find out how ancient civilizations were able to find peace and avoid war--only to find that the key to peace was under their whiskers the whole time.